Biojewel making: an economical and sustainable alternative (International Journal of Geoscience, Engineering and Technology, 2020)
Handicrafts can be defined as “a complex of activities of a manual nature, through which man manifests spontaneous creativity” (Lemos, 2011). In this context, Vale do Jequitinhonha and Mucuri, especially the city of Diamantina-MG, finds a vast field of artisanal work, as a form of income for the poorest populations. Thus, it is in this scenario that biojewels are found as a way of promoting sustainability and valuing Brazilian culture. In view of this, the Tutorial Education Program (PET) created the project Making biojewelry: An economical and sustainable alternative. The objective was to offer activities capable of training participants (short courses, lectures, visits to needy communities) for making biojewels, with products extracted in a sustainable way from nature. It is noteworthy that this process was done as a tool for the search for the reduction of retentions and evasions in the context of UFVJM. The results obtained with the project are undoubtedly beneficial for student participants from a human, social, educational, empathic and economic point of view, mainly related to the conscious use of natural resources. Regarding the issue of decreased retention and evasion, the results are modest, but positive. Thus, it can be concluded that the involvement in the elaboration and creation of handicrafts using natural products, such as biojewels, can contribute positively to the university student and to the community outside the university in order to contribute to the formation of critical, human and preservation of natural resources.